Analysis of Grade 10 High School Students’ Understanding of Renewable Energy Concepts Using the ANATES Application - Munib; Wahab Jufri; Agus Abhi Purwoko; Muh. Makhrus; Joni Rokhmat; AA Sukarso (Postgraduate, University of Mataram, 2026)
The purpose of this study is to evaluate how high school grade X students understand the concepts of renewable energy using the ANATES tool. This study uses a descriptive quantitative approach with a sample of 60 students from two Grade X classes at SMAS Darul Falah Pagutan Mataram. The instrument used was in the form of 20 multiple-choice questions developed based on indicators of understanding renewable energy concepts. The test results were analyzed using ANATES to measure the level of conceptual understanding, the level of difficulty, and the discriminating power. The results showed that 25% of students were in the medium understanding category, 46.7% were in the very low category, and 28.3% were in the low category. Most of the questions were in the medium difficulty category (45%) and had varying discriminating power, with 50% classified as good, 5% as sufficient, and 45% as poor. This study recommends the need to improve learning strategies that emphasize an inquiry-based approach, the contextual integration of ESD (Education for Sustainable Development), and the use of evaluation tools that can provide informative feedback to enhance students' conceptual understanding of renewable energy.